PERIODONTAL CHANGES PERTAINING TO WOMEN FROM PUBERTY TO POSTMENOPAUSAL STAGE - KANAKAM ELIZABETH THOMAS; CHITRA N. (International Journal of Pharma and Bio Sciences, 2013)
A woman from when she attains her puberty till she reaches her menopause is under constant hormonal fluctuation. Changes in Progesterone and estrogen not only bring changes in general health, but also in the oral health. Women when she passes through the different stages, puberty, pregnancy, while on oral contraceptives and menopausal stage, the gingiva tends to get inflamed and leads into gingivitis. This situation if left untreated becomes Periodontitis- inflammation of the gums and tissues surrounding the tooth. The main causative agent of periodontitis is Aerobic and anaerobic bacteria.Women are more prone to periodontitis when compared to men. Hence, oral hygiene and oral health needs to be monitored simultaneously, for a healthier life.